Reversible khat-induced hepatitis: two case reports and review of the literature. Issue 4 (10th May 2013) - Jenkins, M G; Handslip, R; Kumar, M; Mahadeva, U; Lucas, S; Yamamoto, T; Wood, D M; Wong, T; Dargan, P I
Abstract : Recreational chewing of Catha edulis (khat) leaves is part of the ethnic culture of Somali, Yemeni and other East African societies for its stimulant properties. With increasing emigration, khat use has become common in these ethnic groups once they move to other areas such as Europe and the USA; one-third of the UK Somali population report khat use within the last month. Cathinone, the active component of the khat leaves, is controlled under the UK Misuse of Drugs Act, but the use of the khat plant and its leaves remains not subject to control in the UK. There have been several previous reports of acute hepatitis related to chronic use of khat leading to acute liver failure, and resulting in transplantation or death. We report two cases with severe acute khat-related hepatitis that resolved on cessation of khat use initially, but relapsed with further use, reinforcing the importance of permanent khat cessation to prevent progression to liver failure. With reference to the current literature, we also consider the difficult diagnosis of this disorder, then go on to consider the pathophysiology, mechanisms of liver injury and potential future areas of research.